Ecosystem‐level studies of terrestrial carbon reveal contrasting bacterial metabolism in different aquatic habitats. Issue 12 (1st December 2013) - Attermeyer, Katrin; Premke, Katrin; Hornick, Thomas; Hilt, Sabine; Grossart, Hans-Peter
Abstract : In aquatic systems, terrestrial dissolved organic matter (t‐DOM) is known to stimulate bacterial activities in the water column, but simultaneous effects of autumnal leaf input on water column and sediment microbial dynamics in littoral zones of lakes remain largely unknown. The study's objective was to determine the effects of leaf litter on bacterial metabolism in the littoral water and sediment, and subsequently, the consequences for carbon cycling and food web dynamics. Therefore, in late fall, we simultaneously measured water and sediment bacterial metabolism in the littoral zone of a temperate shallow lake after adding terrestrial particulate organic matter (t‐POM), namely, maize leaves. To better evaluate bacterial production (BP) and community respiration (CR) in sediments, we incubated sediment cores with maize leaves of different quality (nonleached and leached) under controlled laboratory conditions. Additionally, to quantify the incorporated leaf carbon into microbial biomass, we determined carbon isotopic ratios of fatty acids from sediment and leaf‐associated microbes from a laboratory experiment using 13 C‐enriched beech leaves. The concentrations of dissolved organic carbon (DOC) increased significantly in the lake after the addition of maize leaves, accompanied by a significant increase in water BP. In contrast, sediment BP declined after an initial peak, showing no positive response to t‐POM addition. Sediment BP and CR were also not stimulated by t‐POM in the laboratory experiment, either in short‐term or in long‐term incubations, except for a short increase in CR after 18 hours. However, this increase might have reflected the metabolism of leaf‐associated microorganisms. We conclude that the leached t‐DOM is actively incorporated into microbial biomass in the water column but that the settling leached t‐POM (t‐POML ) does not enter the food web via sediment bacteria. Consequently, t‐POML is either buried in the sediment or introduced into the aquatic food web via microorganisms (bacteria and fungi) directly associated with t‐POML and via benthic macroinvertebrates by shredding of t‐POML . The latter pathway represents a "benthic shortcut" which efficiently transfers t‐POML to higher trophic levels.